İşgücü açısından Türk banka sistemi ile Avrupa Birliği banka sisteminin bir karşılaştırması - Halıcı, Melek (My University, 2005)
Günümüzde iletişim teknolojilerinin gelişmesi ile mal ve sermaye piyasalarının serbestleşmesi, küreselleşme sürecine hız kazandırmış ve uluslararası finans sisteminin gelişen ekonomilerdeki önemini giderek arttırmıştır. Genel olarak finans sektörü, Türkiye'nin de içinde bulunduğu gelişen ülkelerde ve özellikle gelişmiş AB ülkeleri gibi ülkelerde önemli bir istihdam kaynağı olarak görülmektedir. Genel olarak bankacılık sektöründeki istihdam yapısını ve bu yapı içinde yer alan sektördeki işgücünün eğitim durumu ile kadın-erkek istihdam dağılımını inceleyen bu çalışma, AB ülkeleri ile Türkiye arasındaki bankacılık sektöründeki farklılık ve benzerliklere yer vererek, AB üyelik sürecinde Türk bankacılık sektördeki genel sorunların çözümüne ışık tutmayı amaçlamaktadır. Name and Surname: Melek HALICI Field: Labour Economics and Industrial Relations Programme: Labour Economics Supervisor: Professor Kuvvet LORDOĞLU Degree Awarded and Date: Master - July 2005 Labour Force, Service Sector, Banking, Turkish Banking System, European Union Banking System.

The development of communication technology and liberalisation of the manufacture and capital markets have accelerated the globalisation process and has steadily increased the importance of the international finance system in the developing countries. Finance sector in general terms, is regarded as a crucial employment source in the developing countries such as Turkey and in the already developed EU countries. This study which generally examines the employment structure in the finance sector and educational position of the labour taking part as well as the gender spread, aims to highlight the solutions of the general problems of the Turkish finance sector under the process of Turkey's accession to EU membership by taking into consideration the differences and the similarities in the finance sector between turkey and EU states.
Keywords: Bankalar ve Bankacılık; Ekonomi; Emek ekonomisi; İşgücü_Bankalar